Next-Generation Sequencing Revealed a Distinct Immunoglobulin Repertoire with Specific Mutation Hotspots in Acute Myeloid Leukemia - Miaoran Xia; Lina Wu; Xiaoping Sun; Xin Han; Huige Yan; Jing Huang; Youhui Zhang; Zhihong Hu; Youli Zu; C. Cameron Yin; Xiaoyan Qiu (Biology, 2022)
Immunoglobulin (Ig) is known as a hallmark of B-lymphocytes exerting antibody functions. However, our previous studies demonstrated that myeloblasts from acute myeloid leukemia (AML) patients could also express Ig with distinct roles. Here, we quantified Ig (IGHG and IGK) transcripts by real-time PCR and performed a comprehensive analysis of Ig repertoire (both heavy chains and light chains) in AML blasts. We found that Ig was frequently expressed by AML blasts. A higher level of AML-derived IGHG expression correlated with a significantly shorter disease-free survival. Next-generation sequencing revealed dysregulated transcripts of all five Ig classes (IGHA, IGHD, IGHE, IGHG, and IGHM) and two Ig types (IGK and IGL) in AML. VH-D-JH rearrangements in myeloblasts were biased with individual specificity rather than generally diverse as in B-cells. Compared to AML-derived IgH, AML-derived IGK was more conserved among different AML samples. The frequently shared Vκ-Jκ patterns were IGKV3-20*01/IGKJ1*01, IGKV2D-28*01/IGKJ1*01, and IGKV4-1*01/IGKJ1*01. Moreover, AML-derived IGK was different from classical IGK in B-cells for the high mutation rates and special mutation hotspots at serine codons. Findings of the distinct Ig repertoire in myeloblasts may facilitate the discovery of a new molecular marker for disease monitoring and target therapy.